Arabidopsis AtMSRB5 functions as a salt-stress protector for both Arabidopsis and rice - Cai, Yu-Si; Cai, Jung-Long; Lee, Jent-Turn; Li, Yi-Min; Balladona, Freta Kirana; Sukma, Dewi; Chan, Ming-Tsair (Frontiers in Plant Science, 2023)
Salinity, drought and low temperature are major environmental factors that adversely affect crop productivity worldwide. In this study we adopted an activation tagging approach to identify salt tolerant mutants of Arabidopsis. Thousands of tagged Arabidopsis lines were screened to obtain several potential mutant lines resistant to 150 mM NaCl. Transcript analysis of a salt-stress tolerance 1 (sst1) mutant line indicated activation of AtMSRB5 and AtMSRB6 which encode methionine sulfoxide reductases. Overexpression of AtMSRB5 in Arabidopsis (B5OX) showed a similar salt tolerant phenotype. Further, biochemical analysis indicated stability to the membrane proteins, H+-ATPase 2 (AHA2) through regulation Na+/K+ homeostasis which could be involved in a stress tolerance mechanism. Similarly, overexpression of AtMSRB5 in transgenic rice demonstrated salt tolerant phenotype via the modulation of Na+/K+ homeostasis without a yield drag under salt and oxidative stress conditions.